Kitten care and training - Shojai, Amy (Howell Book House, 2001)
An Owner's Guide to a Happy Healthy Pet is the series to turn to when you want a basic reference that's reliable, up-to-date, and complete. These guides feature: Expert authors, plus renowned guest contributors on specialized topics Full-color photos throughout Basic information on the breed, species, or topic Complete coverage of care, health, grooming, training, and more Tips and techniques to make life with a pet more rewarding